2019
DOI: 10.20882/adicciones.1277
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentos de medida del trastorno de juego en internet en adolescentes y jóvenes según criterios DSM-5: una revisión sistemática

Abstract: The inclusion of Internet Gaming Disorder (IGD) in the DSM-5 has generated controversy over its diagnosis, and it therefore seems necessary to establish a clear cutoff point to identify when excessive gaming becomes problematic. Such identification is especially difficult in adolescents and young people, who frequently dedicate a great deal of time to online games. The goal of this systematic review was to analyze the instruments developed to assess IGD in adolescents and young people since its inclusion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
15
0
4
Order By: Relevance
“…The IGDS9-SF is a sound psychometric test that assesses IGD, and it is one of the most frequently used instruments as it had the greatest number of adaptations to different languages and cultural contexts [56]. In the present study, the development of the Spanish IGDS9-SF was carried out through a rigorous conceptual and methodological procedure that followed conventional international standards [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IGDS9-SF is a sound psychometric test that assesses IGD, and it is one of the most frequently used instruments as it had the greatest number of adaptations to different languages and cultural contexts [56]. In the present study, the development of the Spanish IGDS9-SF was carried out through a rigorous conceptual and methodological procedure that followed conventional international standards [71].…”
Section: Discussionmentioning
confidence: 99%
“…The APA's [21] operationalization of IGD has arguably reduced the diversity in the assessment instruments as well as the number of items contained in each of these instruments, providing more uniform measures with high internal consistency and adequate criterion validity. A systematic review [56] indicated the nine-item Internet Gaming Disorder Scale-Sort Form (IGDS9-SF) [57] as the most reviewed and translated instrument to assess IGD based on the nine IGD criteria developed by the APA. In fact, since its publication, the IGDS9-SF has been translated into at least nine languages: Chinese [58], German [59], Czech [60], Slovenian [61], Italian [62], Persian [63], Turkish [64,65], Polish [66], European and South American Portuguese [67,68].…”
Section: Introductionmentioning
confidence: 99%
“…Entre estos test podemos destacar el Internet Gaming Disorder Scale-20 (Pontes & Griffiths, 2015) adaptado al castellano (Fuster et al, 2016), el Internet Gaming Disorder Scale-short form -9 (Pontes & Griffiths, 2015) y su adaptación española (Beranuy et al, 2020) y el Cuestionario de Experiencias Relacionadas con Videojuegos (CERV) (Chamarro et al, 2014). También se puede consultar la revisión de los instrumentos de medida para jóvenes y adolescentes según criterios DSM-5 (Bernaldo- de-Quirós et al, 2019). Pese al avance que suponen siguen siendo necesarios más estudios con población clínica (Bernaldo-de-Quirós et al, 2019).…”
Section: Ventajasunclassified
“…Mientras que en el caso de los adultos los 12 meses que se requieren para el diagnóstico son útiles para distinguir un trastorno mental de un malestar transitorio, en niños y adolescentes este periodo de tiempo puede ser demasiado extenso. Sin embargo, se hace difícil establecer de forma clara y precisa lo que es un jugador social, excesivo, problemático y adictivo especialmente en adolescentes y jóvenes (Bernaldo- de-Quirós et al, 2019;Carbonell et al, 2016). Una alternativa seria recurrir a usar herramientas diagnósticas que permitan una evaluación de la gravedad con puntuaciones normalizadas, sin recurrir a criterios diagnósticos (Bernaldode-Quirós et al, 2019).…”
Section: Retos Y Oportunidadesunclassified
“…The Worlds Health Organization also included Gaming Disorders in the actual version of the International Classification of Diseases (ICD-11) [9]. The measurement instruments and the consequences of Gaming Disorders are widely debated [10, 11]. Studies investigating video gaming (gaming time between 50 and 165 minutes) and sleep have shown variable effects on sleep and stress, the latter typically expressed as heart rate changes [12, 13].…”
Section: Introductionmentioning
confidence: 99%